Host age and Plasmodium falciparum multiclonality are associated with gametocyte prevalence: a 1-year prospective cohort study - Yaw Adomako-Ankomah (Malaria Journal, 2017)
Abstract Background Since Plasmodium falciparum transmission relies exclusively on sexual-stage parasites, several malaria control strategies aim to disrupt this step of the life cycle. Thus, a better understanding of which individuals constitute the primary gametocyte reservoir within an endemic population, and the temporal dynamics of gametocyte carriage, especially in seasonal transmission settings, will not only support the effective implementation of current transmission control programmes, but also inform the design of more targeted strategies. Methods A 1-year prospective cohort study was initiated in June 2013 with the goal of assessing the longitudinal dynamics of P. falciparum gametocyte carriage in a village in Mali with intense seasonal malaria transmission. A cohort of 500 individuals aged 1–65 years was recruited for this study. Gametocyte prevalence was measured monthly using Pfs25-specific RT-PCR, and analysed for the effects of host age and gender, seasonality, and multiclonality of P. falciparum infection over 1 year. Results Most P. falciparum infections (51–89%) in this population were accompanied by gametocytaemia throughout the 1-year period. Gametocyte prevalence among P. falciparum-positive individuals (proportion of gametocyte positive infections) was associated with age (p = 0.003) but not with seasonality (wet vs. dry) or gender. The proportion of gametocyte positive infections were similarly high in children aged 1–17 years (74–82% on median among 5 age groups), while older individuals had relatively lower proportion, and those aged > 35 years (median of 43%) had significantly lower than those aged 1–17 years (p < 0.05). Plasmodium falciparum-positive individuals with gametocytaemia were found to have significantly higher P. falciparum multiclonality than those without gametocytaemia (p < 0.033 in two different analyses). Conclusions Taken together, these results suggest that a substantial proportion of Pf-positive individuals carries gametocytes throughout the year, and that age is a significant determinant of gametocyte prevalence among these P. falciparum-positive individuals. Furthermore, the presence of multiple P. falciparum genotypes in an infection, a common feature of P. falciparum infections in high transmission areas, is associated with gametocyte prevalence.